The Role of Tele-Orthodontics in Enhancing Patient Compliance and Treatment Monitoring - Salem Almoammar (Wolters Kluwer Medknow Publications, 2024)
Background: Tele-orthodontics, the application of telecommunications technology in orthodontic care, has emerged as a promising tool to enhance patient compliance and facilitate treatment monitoring. In traditional orthodontic practice, patient compliance and monitoring are pivotal but often challenging aspects. Tele-orthodontics offers a solution by providing remote communication and monitoring capabilities, potentially improving patient engagement and treatment outcomes. Materials and Methods: This study conducted a retrospective analysis of orthodontic patients who utilized tele-orthodontics as part of their treatment plan. A total of 100 patients were included in the study, with ages ranging from 12 to 40 years old. Patients were provided with mobile applications or web-based platforms enabling them to communicate with their orthodontists, submit progress images, and receive feedback remotely. Treatment compliance was assessed based on adherence to scheduled appointments, wearing of orthodontic appliances, and completion of prescribed exercises. Results: The analysis revealed a significant improvement in patient compliance with the implementation of tele-orthodontics. Adherence to scheduled appointments increased by 30%, with patients attending 95% of their appointments compared to 65% before the introduction of tele-orthodontics. Moreover, compliance with wearing orthodontic appliances showed a remarkable rise, with patients consistently wearing their appliances for an average of 22 h per day, up from 14 h per day previously. Additionally, the completion rate of prescribed exercises saw a notable enhancement, with 80% of patients completing their exercises as instructed, compared to 50% previously. Conclusion: Tele-orthodontics plays a significant role in enhancing patient compliance and treatment monitoring in orthodontic care. The remote communication and monitoring capabilities provided by tele-orthodontic platforms empower patients to actively participate in their treatment process, leading to improved adherence to appointments, better compliance with wearing orthodontic appliances, and increased completion of prescribed exercises. These findings underscore the importance of integrating tele-orthodontics into orthodontic practice to optimize patient outcomes and satisfaction.